2015
DOI: 10.1371/journal.pone.0118415
|View full text |Cite
|
Sign up to set email alerts
|

Function and Evolutionary Origin of Unicellular Camera-Type Eye Structure

Abstract: The ocelloid is an extraordinary eyespot organelle found only in the dinoflagellate family Warnowiaceae. It contains retina- and lens-like structures called the retinal body and the hyalosome. The ocelloid has been an evolutionary enigma because of its remarkable resemblance to the multicellular camera-type eye. To determine if the ocelloid is functionally photoreceptive, we investigated the warnowiid dinoflagellate Erythropsidinium. Here, we show that the morphology of the retinal body changed depending on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…A noteworthy example of complex structural morphogenesis involving symbiogenesis was recently reported in Warnowiid dinoflagellates, which are remarkable unicellular organisms possessing camera eye-like ocelloids for capturing light. 33,34 Analysis of different ocelloid components showed that the cornea was formed by mitochondria and the retina by red algae-derived plastids. 35 Apparently, this early eye-like organelle arose through sequential cell mergers and did not form "by numerous, successive, slight modifications" as Darwin postulated in Origin of Species.…”
Section: Multiple Cell Fusions In the Evolution Of Photosynthetic Eukmentioning
confidence: 99%
“…A noteworthy example of complex structural morphogenesis involving symbiogenesis was recently reported in Warnowiid dinoflagellates, which are remarkable unicellular organisms possessing camera eye-like ocelloids for capturing light. 33,34 Analysis of different ocelloid components showed that the cornea was formed by mitochondria and the retina by red algae-derived plastids. 35 Apparently, this early eye-like organelle arose through sequential cell mergers and did not form "by numerous, successive, slight modifications" as Darwin postulated in Origin of Species.…”
Section: Multiple Cell Fusions In the Evolution Of Photosynthetic Eukmentioning
confidence: 99%
“…the same way that ciliary and microvillar photoreceptor cells in animals maximize photosensitivity. This should be remedied by collecting them in the tropical pacific waters where they are most abundant [68]. This is the case in other algae with channelrhodopsins (e.g.…”
Section: Rare Dinoflagellates Sculpted Organelles Into Eyelike "Ocellmentioning
confidence: 99%
“…Hayakawa et al purportedly localized bacteriorhodopsin mRNAs to the retinal body in Erythropsidinium [68]. But these results should be taken with some caution, since rhodopsin was found to be nuclear-encoded in most if not all other eukaryotic studies (making it unlikely to reside in the retinal body plastome).…”
Section: Rare Dinoflagellates Sculpted Organelles Into Eyelike "Ocellmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayakawa et al. () and Gavelis et al. () carried out the immune‐cytological and genomic studies, and new TEM studies in warnowiid dinoflagellates.…”
mentioning
confidence: 99%